An empirical study of the limits and perspectives of institutional transfers - Marie Möller (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2012)
The aim of this paper is to determine which country-specific characteristics promote and which impede the adoption of institutions. On the basis of a broad panel of 183 countries for the period between 1996 and 2010, we test whether there are tendencies towards a general improvement and towards a convergence of institutional quality. Based on the hypothesis that younger countries tend to adopt the smoothly functioning institutions of older ones, we ana-lyze which of the younger countries have good institutions and why. Among other things, we found that older countries do have better institutions than younger ones, but it is questionable that there is a causal effect. Moreover, the results of our empirical investigation show that having been a UK colony or the degree of economic openness have no effect on the institu-tional quality; while on the other hand, religion, region and dependency on natural resources do indeed have such effects. In addition, the potential role of international organizations with regard to nation building and institutional transfer is discussed. – – Ziel des Aufsatzes ist es herauszufinden, welche länderspezifischen Ei-genschaften institutionellen Transfer hemmen oder begünstigen. Auf Basis eines Panels, das 183 Länder über den Zeitraum 1996-2010 umfasst, wird untersucht, ob eine generelle Verbes-serung der institutionellen Qualität im Zeitverlauf sowie eine Tendenz hin zu Konvergenz zu beobachten ist. Basierend auf der Hypothese, dass jüngere Länder dazu tendieren, die Institu-tionen älterer Länder, die sich bewährt haben, zu übernehmen, wird in diesem Aufsatz unter-sucht, welche der jüngeren Länder gute Institutionen haben und warum. Es zeigt sich, dass Länder die bereits lange unabhängig waren, tatsächlich über bessere Institutionen verfügen, dies lässt sich allerdings nicht kausal auf die Dauer der Unabhängigkeit zurückführen. Die Ergebnisse der empirischen Analyse zeigen darüber hinaus, dass die Offenheit einer Volks-wirtschaft sowie die Frage, ob es sich um eine ehemalige Kolonie Großbritanniens handelt keinen Effekt auf die Qualität der Institutionen haben, während Religion, Region und Res-sourcenabhängigkeit Effekte aufweisen. Überdies wird die Rolle von Internationalen Organi-sationen in Bezug auf Nation Building und Institutionentransfer diskutiert.
Keywords: 330; Institutions; Democracy; Nation Building; Freedom; Democracy Indices; Institutionen; Demokratie; Nation Building; Freiheit; Demokratieindikatoren